Garra roseae, a new species from the Makran region in southern Iran (Teleostei: Cyprinidae) - Mousavi-Sabet, Hamed; Saemi-Komsari, Maryam; Doadrio, Ignacio; Freyhof, Jörg (Zootaxa, 2019)
Garra roseae, new species, is described from the stream Tang-e-Sarhe in the Iranian Makran region. It is distinguished from its congeners in the Middle East by lacking barbels, having a small mental disc, 42–58 total scales along the lateral line, 24–30 scales along the predorsal midline, and 20–24 circumpeduncular scales. It is further characterised by having five diagnostic nucleotide substitutions and a minimum K2P distance of 5.39% to G. rossica and 5.49% to G. nudiventris in the mtDNA COI barcode region. Garra phryne from eastern Iran is considered to be a synonym of G. nudiventris.